EFEKTIVITAS PENERAPAN MODEL DISCOVERY LEARNING TERHADAP PENINGKATAN HASIL BELAJAR PESERTA DIDIK KELAS XI MAN 3 PEKANBARU PADA MATERI MATRIKS - Khairani, Bella Putri; Murni, Atma; Yuanita, Putri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The background of this research is the low outcomes study of mathematical  of students class XI MAN 3 Pekanbaru. The purposes of this research are (1) to describe the difference of mathematical outcomes study of students who study through discovery learning (DL) model with student who study through conventional learning with scientific approaching; (2) to describe the improvment of mathematical outcomes study of students who study through discovery learning (DL) model with students who study through conventional learning with scientific approaching. This research is an experimental research (quasi experiment) with The Nonequivalent Pretest-Posttest Control Group Design. The population of this research is all students of class XI MAN 3 Pekanbaru. The sample of this research consits of two classes, class XI MIA2 as experiment class and XI MIA1 as control class. The research instruments are mathematical prior knowledge test and matehmatical outcomes study test. Mathematical prior knowledge test score were used to select the sample of this research. Data were analysed by using Independent sample t-test preceded by normality test and homogenity of variances test. The result showed that the difference of mathematical and the improvement of mathematical outcomes study of students who study through DL model is higher than student who study through conventional learning with scientific approaching.  Key Words: Discovery Learning, Mathematical Outcomes Study